Effect of vitamin C upon Selective Serotonin Reuptake Inhibitors (SSRIs) treated Obsessive Compulsive Disorder Patients: A randomized controlled clinical trial in Bangladesh (Bangladesh Critical Care Journal, 2023)
Objective: To assess the efficacy of vitamin C as an adjunct to Selective Serotonin Reuptake Inhibitors (SSRIs) intreating OCD patients.Design: Single-blind randomized controlled trial.Study eligibility: Randomly selected 96 OCD patients diagnosed by the psychiatric consultants following the DSM-5criteria of both sexes aged 18 years and above were initially enrolled; finally, 83completed the study. The study wasconducted at Bangabandhu Sheikh Mujib Medical University (BSMMU) in Dhaka, Bangladesh, from March 2018 toFebruary 2019.Interventions: After obtaining written informed consent, participants were randomly divided into group A (controlgroup) and group B (intervention group). A baseline recording of the body's endogenous antioxidant markers (plasmavitamin C and erythrocyte glutathione levels), oxidative stress marker (plasma malondialdehyde), and Yale-Brownscore of OCD by Yale-Brown Obsessive-Compulsive Scale(Y-BOCS) were measured in both groups. The control group(n=40) received oral SSRIs daily for eight weeks, while the intervention group (n=56) received the SSRIs plus oralvitamin C (500 mg twelve hourly) daily for the same duration. The biochemical parameters and the Y-BOCS score ofOCD of both groups were obtained after eight weeks, and the result was analyzed and compared.Main outcome measures: The outcomes were levels of plasma vitamin C, erythrocyte (RBC) glutathione and plasmamalondialdehyde, and the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS).Result: Baseline recordings suggest significantly (p0.05) higher levels of plasma MDA concentrations in both groups. After eightweeks of intervention with vitamin C plus SSRIs, plasma vitamin C and RBC glutathione levels were significantly(p